2007
DOI: 10.1016/j.bbamem.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Segment TM7 from the cytoplasmic hemi-channel from VO-H+-V-ATPase includes a flexible region that has a potential role in proton translocation

Abstract: A 900-MHz NMR study is reported of peptide sMTM7 that mimics the cytoplasmic proton hemi-channel domain of the seventh transmembrane segment (TM7) from subunit a of H(+)-V-ATPase from Saccharomyces cerevisiae. The peptide encompasses the amino acid residues known to actively participate in proton translocation. In addition, peptide sMTM7 contains the amino acid residues that upon mutation cause V-ATPase to become resistant against the inhibitor bafilomycin. 2D TOCSY and NOESY (1)H-(1)H NMR spectra are obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…While the cytosolic orientation of the N-terminal tail is generally accepted, its transmembrane topology remains controversial as recently discussed. (55) So far a six, (57,58) eight, (59,60) and nine (61,62) transmembrane helix topological model of the membraneembedded part of a has been proposed. According to the topology model with eight transmembrane helixes, both N-and the C-terminal tails of a isoforms (Vph1p and Stv1p) are located in the cytosol, which is supported by experimental data, showing interaction of phosphofructokinase-1 with the C-terminal tail of the human a4 and a1 isoforms.…”
Section: Structural Features Of the Membrane-embedded A 0 Sectormentioning
confidence: 99%
See 3 more Smart Citations
“…While the cytosolic orientation of the N-terminal tail is generally accepted, its transmembrane topology remains controversial as recently discussed. (55) So far a six, (57,58) eight, (59,60) and nine (61,62) transmembrane helix topological model of the membraneembedded part of a has been proposed. According to the topology model with eight transmembrane helixes, both N-and the C-terminal tails of a isoforms (Vph1p and Stv1p) are located in the cytosol, which is supported by experimental data, showing interaction of phosphofructokinase-1 with the C-terminal tail of the human a4 and a1 isoforms.…”
Section: Structural Features Of the Membrane-embedded A 0 Sectormentioning
confidence: 99%
“…Cysteine cross-linking experiments demonstrated that helix TM7 of a subunit is in the proximity to TM4 of c and c 0 subunits and to TM3 of c 00 subunit, containing Glu residues, essential for proton translocation during rotation of the c ring. (62) Based on this data, the model of swiveling of interacting helices in a and c of the proteolipid ring was suggested. This swiveling could control the access of protons to the hemi-channels of subunit a during proton-pumping activity.…”
Section: Structural Features Of the Membrane-embedded A 0 Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…1) (Duarte et al 2007a, b; Vos et al 2007) . These putative transmembrane peptides include the arginine residue (R735), which is known to be part of the proton translocation channel, interacting with the glutamic acids from the subunits c, c′, and c″ (Nishi and Forgac 2002).…”
Section: Introductionmentioning
confidence: 99%